Branding Image of Higher Education Quality Based on Islamic Boarding Schools - Khoiroh, Muhimmatul; Aziz, Abd.; Fatimah, Nur (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to describe the branding image development strategy of Islamic boarding school-based higher education. The study elevates the branding "Khairu Ummah Rahmatal Lil'alamin" as an institutional identity that combines academic excellence and Islamic values. This study uses a qualitative approach with a content analysis method. This research was conducted at Zainul Hasan Genggong Islamic University. Data were collected through in-depth interviews, observations, and documentation, then analyzed using Miles and Huberman's interactive analysis techniques. The results of the study indicate that the branding strategy is carried out through strengthening religious values, improving the quality of academic services, and optimizing digital and traditional promotional media. The main supporting factors are the strong commitment of campus managers and the involvement of the academic community, while the main challenges come from competition between universities and changes in community preferences. This study recommends the need for continuous innovation to maintain the relevance of branding amidst the development of the times.